1970
DOI: 10.1021/ac50160a064
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stability of sulfur dioxide in solution

Abstract: room temperature, the black precipitate was isolated by filtration through a dry, weighed, medium porosity, sintered glass funnel; washed thoroughly with methanol, acetone, and chloroform; dried in a vacuum desiccator; and weighed.Tellurium Complexes. Addition of tellurium (recovered from analyses) to an excess of bromine in a mixture of pyridine and methanol afforded a red complex, mp 310 °C (dec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Over an appropriate time period, aliquots of sample were withdrawn and analyzed for sulfur dioxide by the West-Gaeke procedure. Scaringelli et al (1970) indicated that the sulfur dioxide oxidation reaction is first-order and that it follows the equation In Co = natural log of concentration at time zero Present studies confirm this first-order reaction plot. Data from these plots are presented in Table III.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Over an appropriate time period, aliquots of sample were withdrawn and analyzed for sulfur dioxide by the West-Gaeke procedure. Scaringelli et al (1970) indicated that the sulfur dioxide oxidation reaction is first-order and that it follows the equation In Co = natural log of concentration at time zero Present studies confirm this first-order reaction plot. Data from these plots are presented in Table III.…”
supporting
confidence: 59%
“…; Scaringelli etal., 1967bal., : Scaringelli et al, 1970 Lahmann, 1969;Perry and Tabor, 1962), but only little reference has been made to the effect of temperature or concentration of tetrachloromercurate(II) on the stability of the complex species. It was deemed necessary, therefore, to include a…”
mentioning
confidence: 99%
“…The presence of EDTA improves the stability of SO2 in solution. 28 Calibration and standardization of the analytical procedure may be accomplished by use of accurately calibrated flowmeters and a plot of the absorbance of standard sulfite solutions. Alternatively, known amounts of SO2 in air may be prepared by use of permeation tubes at constant temperature and an appropriate gas dilution system.…”
Section: Sulfur Dioxidementioning
confidence: 99%
“…2,3 A number of investigations have been reported that have aimed to minimize the interference due to impurities in the dye, ozone, oxides of nitrogen and transition metal ions. [4][5][6][7][8][9][10] The addition of the dye for colour development during the chemical analysis stage plays an important role. Usually, pararosaniline hydrochloride (PRA) dye is used in this method.…”
Section: Introductionmentioning
confidence: 99%